PENERAPAN SENAM KAKI UNTUK MENURUNKAN KADAR GULA DARAH PASIEN DIABETES MELITUS TIPE 2 YANG SEDANG MENJALANI PERAWATAN DIRUMAH SAKIT UMUM DAERAH BAYU ASIH PURWAKARTA - Teten Rustendi; Grace Evelyn (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Type 2 diabetes melitus is a condition where blood sugar is high in the body. According to data on WHO 2020 diabetes melitus attacks approximately 422 milion people and causes 1.6 million deaths. Signs of frequent urination, feeling thirsty, i’m tired, visibility disorder, and lose weight. The exercise of diabetes lactus feet is intended to control or lower blood sugar levels in diabetes melitus patients. The results of using therapy 1 time a day for 3 days, on the first day before the application was applied to get results: 390 mg/dl after the application dropped to 370 mg/dl, day two before application get results: 350 mg/dl after application decreased to: 335 mg/dl, day three before application get results: 290 mg/dl after application decreased to: 278 m/dl. After therapy 1 times in 3 are the decreasing blood sugar levels of 390 mg/dl to 278 mg/dl. Recommendation: health care is expected to apply leg gymnastic as therapy to lower blood sugar levels in diabetes melitus patients